Imaginarios sociales de la enseñanza del español como lengua extranjera en Colombia (2019)
This work proposes the study of social imaginaries (Taylor, Castoriadis, Velásquez) that some foreigners in Colombia have about the teaching of Spanish as a foreign language (ELE). Therefore, it is proposed that the identification of the social imaginaries that foreigners who wish to learn Spanish in Colombia have corresponds to an object of study that generates new conceptual edges for the configuration of proposals for teaching Spanish as a Foreign Language according to the needs of the context.